The girl who drew butterflies : how Maria Merian's art changed science - Sidman, Joyce (Houghton Mifflin Harcourt, 2018)
"Explores the extraordinary life and scientific discoveries of Maria Merian, who discovered the truth about metamorphosis and documented the science behind the mystery in this visual biography that features many original paintings by Maria herself."--